Improving Personal Competence of Teacher in Remote Areas Based on Mental Revolution - Dodo Sutardi; Dihamri; Nurmintan Silaban (International Conference on Education, Islamic Studies and Social Sciences Research)
Teachers’ problems in remote areas was massive absenteeism. According to the Education Sector Analytical and Capacity Development Partners, 2014, teachers absenteeism in remote areas reached 20%, while in urban areas was 9.4%. Teacherbecame defaulters teaching because of heir low personal competence. There was no available training that focused on improving remote areas teachers ownompetence. One method that could be conducted is by applying mental revolution movement. The objective of the study was to examine the effectiveness of mental revolution in improving the personal competence of primary school teachers in remote areas.The quasi-eksperiment model with One-Group Pretest-Posttest Design was used in the study.The participants in the study were 38 elementary shoolteacherswho were a civil servant in remote areas in Bengkulu Province. The result in this research explained that the implementation of mental revolution based on local wisdom could improve the personal competence of civil servant elementaryschool in remote areas in Seluma District in Bengkulu Province